PENGARUH PENEMPATAN KERJA, KOMUNIKASI, KOMPENSASI DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. TRAKINDO UTAMA PEKANBARU - Ratih Anggraini Siregar (Jurnal Prodi Fakultas Ekonomi-UISU, 2019)
This research aims to examine and analyze the influence of work placement, communication, compensation and motivation to work on employee achievement at PT. Trakindo Utama Pekanbaru. This study uses an associative quantitative research. This study uses primary data where data is collected using questionnaires. This research was conducted by PT. Trakindo Utama Pekanbaru with a population of 98 employees and samples of 98 respondents. The data analysis techniques in this study used descriptive statistics, classical assumption tests, some linear regression analyses, hypothesis testing and coeficient test determination. The results of the analysis show that work placement affects employees ' work achievement. Communication affects employees ' working achievements. Compensation affects the achievement of work. Work motivation affects work achievement. The results of the analysis proved that simultaneously the placement of work, communication, compensation and motivation to work on the employees ' work achievement jointly PT. Trakindo Utama Pekanbaru.Keywords: Job placement, communication, compensation, work motivation, job performance